Enhancement of the oxygen reduction on nitride stabilized pt-M (M=Fe, Co, and Ni) core–shell nanoparticle electrocatalysts. (April 2015) - Kuttiyiel, Kurian A.; Choi, YongMan; Hwang, Sun-Mi; Park, Gu-Gon; Yang, Tae-Hyun; Su, Dong; Sasaki, Kotaro; Liu, Ping; Adzic, Radoslav R.
Abstract: Given the harsh operating conditions in hydrogen/oxygen fuel cells, the stability of catalysts is one of the critical questions affecting their commercialization. We describe a distinct class of oxygen reduction (ORR) core–shell electrocatalysts comprised of nitride metal cores enclosed by thin Pt shells that is easily synthesized. The synthesis is reproducible and amenable to scale up. Our theoretical analysis and the experimental data indicate that metal nitride nanoparticle cores could significantly enhance the ORR activity as well as the durability of the core–shell catalysts as a consequence of combined geometrical, electronic and segregation effects on the Pt shells. In addition to its fuel cells application, this class of catalysts holds promise to significantly contribute in resolving the problem of platinum scarcity and furthermore indicates the guidelines for future research and development. Graphical abstract: Highlights: The non-precious metal nitrided core changes the geometric and electronic structure of PtMN/C catalysts. Nitriding increases the stability of the core-shell catalyst. DFT calculations have shown PtNiN/C at the top of the volcano curve.